Valorization of the chemical diversity of the tropical red seaweeds Acanthophora and Kappaphycus and their applications in aquaculture: A review - Guillén, Paúl O.; Motti, Pierfrancesco; Mangelinckx, Sven; De Clerck, Olivier; Bossier, Peter; Van Den Hende, Sofie (Frontiers in Marine Science, 2022)
Graphical Abstract